RELATIONSHIP BETWEEN SYNTHETIC COTTON DUST EXPOSURE AND SYMPTOMS OF RESPIRATORY DISORDERS IN TEXTILE FACTORY WORKERS AT PT X IN EAST JAVA - Desdiani, Desdiani; Soemarko, Dewi Sumaryani; Purnama, Ahmad Angga (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Respiratory disorders, which range from 1 to 100 μm, are a significant concern in the textile industry. Typical symptoms of cotton dust exposure include chronic cough with or without phlegm, painful breathing, wheezing, nasal congestion, and chest pain. While most research has focused on natural cotton fibers, there is a growing need to investigate the health risks associated with synthetic cotton dust, such as that derived from petroleum-based resources such as polyester. Method. This research employed a cross-sectional design, with 76 respondents. Result & Analysis. The results showed that 21.1% of the workers experienced respiratory symptoms, and 43.4% of the workers were exposed to high levels of synthetic cotton dust. Chi-square test analysis indicated a significant relationship between synthetic cotton dust exposure and respiratory symptoms (p < 0.001; OR 15.1 [3.17 – 73.21]). Discussion. Workers with high synthetic cotton dust exposure had a 15.1 times greater risk of experiencing respiratory symptoms than those with low synthetic cotton dust exposure.